Is Islam Compatible With Democracy? Islamist Movement’s Trajectory on Democratization in Indonesia - Muzayyin Ahyar (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2017)
The democratization process in Indonesia is in line with the emergence several Islamic mass organizations which accept or rejected the concept of democracy. Since the pre-independence era, Indonesia has been facing some Islamist groups that opposed to state’s ideology of democracy. This article presents the discussion among scholars about the compatibility between Islamic norms and democratic values, and in what position Indonesia is. The dealing question with the discussion is; does the proliferation of radical Islamist movement signify the incompatibility of Islam and democracy? By using sociological and historical approach, this paper analyzes in order to what extent the values of democracy and Islamism adapt in the frame of a democratic country. The analysis of this research results that the existing radical Islamist movement is not a failure of Indonesia’s effort to harmonize Islam with democracy. Thus, neither the presence of pro-democracy Islamic mass organizations nor the radical Islamist movement cannot be used as the final argument to answer whether Islam compatible with democracy or not. The results of this study reveal that democratization in Indonesia has been accompanied by the proliferation of Islamist movements. The proliferation of Islamist movements nowadays precisely indicates that democracy in Indonesia has a special experience regarding new formula of peacefully religion-state relations.